AGU 610 — International Business Management - February 2000 - PPP, Pusat Pengajian Pengurusan (2000)
UNIVERSITI SAINS MALAYSIA Master Of Business Administration Second Semester Examination Academic Session 1999/2000 February 2000 AGU 610 — International Business Management Time: [ 3 hours]